ANALISIS KEMANDIRIAN BELAJAR SISWA KELAS X SMK DALAM PEMBELAJARAN MATEMATIKA - Yandra, Fadila Ananda; Haerudin, Haerudin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to analyze and describe the learning independence possessed by students of class X TBSM SMK Al Fathimiyah. The method used in this study is a descriptive qualitative research method using 29 students from class X TBSM SMK Al Fathimiyah as research subjects. The instrument used in this study was a non-test instrument in the form of a student learning independence questionnaire consisting of 30 statements. The data collection technique in this study was carried out by distributing questionnaires. Data analysis techniques by making the percentage of student answers are then described using the criteria for the percentage of student answers. The results showed that the average percentage of students' answers on the attitude scale questionnaire for students' mathematics learning independence was 71.55%. This indicates that most students of class X TBSM Al Fathimiyah have an independent attitude in learning. However, students still have to improve their learning independence so that each indicator in learning independence can be improved even better.